Impaired Notch‐MKP‐1 signalling in hidradenitis suppurativa: an approach to pathogenesis by evidence from translational biology. Issue 3 (12th March 2013) - Melnik, Bodo C.; Plewig, Gerd
Abstract Recent findings in familial hidradenitis suppurativa (HS) demonstrated loss‐of‐function mutations of components of the γ‐secretase (GS) complex leading to decreased protease cleaving activity, which may compromise canonical Notch signalling. Appropriate Notch signalling is of pivotal importance for maintaining the inner and outer root sheath of the hair follicle and skin appendages. This viewpoint on the pathogenesis of HS is primarily supported by circumstantial evidence derived from translational biology. Impaired Notch signalling is proposed to be the major pathogenic mechanism of HS. Deficient Notch signalling switches the fate of outer root sheath cells, resulting in conversion of hair follicles to keratin‐enriched epidermal cysts. Impaired Notch signalling may compromise apocrine gland homoeostasis as well. Damage‐associated molecular pattern molecules released by either ruptured epidermal cysts exposing keratin fibres or altered structural components of less maintained apocrine glands may both stimulate TLR‐mediated innate immunity. All aggravating factors of HS, that is, smoking, obesity, skin occlusion, androgens and progesterone, may further promote inflammation by release of proinflammatory cytokines derived from activated monocyte/macrophages. Inappropriate Notch signalling may not only initiate inflammation in HS but may lead to insufficient feedback inhibition of overstimulated innate immunity. Regular Notch signalling via induction of MAPK phosphatase‐1 (MKP‐1) terminates TLR‐MAPK‐signalling in macrophages and IL‐23 secreting DCs, the key players for Th17 cell polarization. Thus, impaired Notch signalling links HS to other Th17‐driven comorbidities. All major therapeutic interventions in HS appear to attenuate increased MAPK activation of innate immune cells due to impaired Notch‐mediated feedback regulation of innate immunity.